DEMAK GREEN GARDEN : OASE HIJAU DI JANTUNG TANAH WALI - Nafisatur Rohmah; Cahyani Dwi Arsanti; Muhammad Imam Taqiyyudin; Melinda Puspita; Najwa Zakial Faza; Noor Fatmawati (Jurnal Komunikasi dan Budaya, 2024)
Demak Green Garden (DeGeGa) is the largest family tourist attraction in Demak Regency, Central Java. DeGeGa has an area of around 120 hectares and offers a variety of tourist facilities and attractions, ranging from gardens, swamps, rice fields, to rides. This journal aims to analyze DeGeGa's potential as a family tourism destination. The research was conducted using qualitative methods, with data collection techniques in the form of interviews, observation and documentation. The research results show that DeGeGa has great potential as a family tourism destination. DeGeGa has a variety of facilities and tourist attractions that are interesting and educational for children and families. Apart from that, DeGeGa also has a strategic location, namely near the city of Demak, which is one of the religious tourism destinations in Central Java. However, DeGeGa also has several challenges that need to be overcome, such as lack of promotion and management that is not yet optimal. To overcome these challenges, efforts are needed to increase DeGeGa promotion and improve its management.